Remote drug loading into liposomes via click reaction. Issue 7 (18th May 2022) - Zheng, Yaxin; Xie, Lei; Tie, Xiaoru; Cao, Lei; Li, Qingyuan; Quan, Yue; Tang, Lingfeng; Li, Yang
Abstract : We developed a click reaction-mediated active loading strategy, in which the drug loading was achieved by the generation of hydrophilic products in the liposome's lumen from the click reaction of glutathione with drug-maleimide conjugates. Abstract : The development of liposome-based drugs was severely limited due to inefficient loading strategies. Herein, we developed a click reaction-mediated loading procedure by designing an enzyme-sensitive maleimide (MAL) tag for ferrying chemotherapeutics into preformed liposomes containing glutathione (GSH). Based on this strategy, various hydrophobic drugs could be encapsulated into liposomes within 5–30 min with encapsulation efficiency >95% and loading capacity of 10–30% (w/w). The entrapped cargo could be slowly released from the liposomes, followed by rapid enzyme-mediated conversion into active drugs to exert antitumor activity under physiological conditions. The resulting drug-loaded liposomes significantly prolonged the blood circulation of cargos and displayed more potent in vivo antitumor efficacy than free drugs at the equitoxic dose. More importantly, this method is a remote drug loading strategy in nature, which is suitable for industrial production. This is the first demonstration of active loading of MAL-tagged chemotherapeutics in liposomes for improved antitumor efficacies, which has the potential to serve as a universal drug loading strategy for the development of liposomal formulations of chemotherapeutics.